TypeRighting: Combining the Benefits of Handwriting and Typeface in Online Educational Videos - Thies, Bill; Cutrell, Ed; Cross, Andrew (2013)
Recent years have seen enormous growth of online educational videos, spanning K-12 tutorials to university lectures. As this content has grown, so too has grown the number of presentation styles. Some educators have strong allegiance to handwritten recordings (using pen and tablet), while others use only typed (PowerPoint) presentations. In this paper, we present the first systematic comparison of these two presentation styles and how they are perceived by viewers. Surveys on edX and Mechanical Turk suggest that users enjoy handwriting because it is personal and engaging, yet they also enjoy typeface because it is clear and legible. Based on these observations, we propose a new presentation style, TypeRighting, that combines the benefits of handwriting and typeface. Each phrase is written by hand, but fades into typeface soon after it appears. Our surveys suggest that about 80% of respondents prefer TypeRighting over handwriting. The same fraction of respondents prefer TypeRighting over typeface, for videos in which the handwriting is sufficiently legible.